2019
DOI: 10.11604/pamj.2019.34.25.16755
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dog population in Nasarawa state Nigeria: a pilot study

Abstract: IntroductionEstimation of dog population is relevant in Animal Health Planning; some of the benefits include rabies control and possible elimination, estimation of quantity of dog vaccines and drugs required in the state, policy development and implementation.MethodsA cross-sectional study was conducted to estimate the population of dogs in Nasarawa state; a local government area (LGA) was randomly selected from each of the three senatorial districts and two wards were selected randomly from the selected LGA's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
4
5
3
Order By: Relevance
“…However, this does not agree with the findings of Kwaghe et al, (2019); Hambolu et al (2014) who reported higher female to male dog ratio. Dogs were mostly kept for security purposes.…”
Section: Incidence and Management Of Dog Bites In Kwara Statecontrasting
confidence: 98%
See 3 more Smart Citations
“…However, this does not agree with the findings of Kwaghe et al, (2019); Hambolu et al (2014) who reported higher female to male dog ratio. Dogs were mostly kept for security purposes.…”
Section: Incidence and Management Of Dog Bites In Kwara Statecontrasting
confidence: 98%
“…Most of the owned dogs were local breeds. This aligns with reports from Kwaghe et al, (2019) and Grace et al, (2018).…”
Section: Incidence and Management Of Dog Bites In Kwara Statesupporting
confidence: 93%
See 2 more Smart Citations
“…A myriad of challenges such as poor awareness and knowledge of rabies, lack of political will, shortage of vaccines, and other vaccine-related factors has led to the endemicity of rabies and significant under-reporting of rabies in Nigeria [10]. Moreover, the presence of free-roaming dogs has complicated rabies elimination in Africa and Asia [11][12][13]. Globally, eradication of canine rabies combined with post-exposure prophylaxis is widely considered as the most cost-effective means of eradicating human rabies [14,15].…”
Section: Introductionmentioning
confidence: 99%